2012
DOI: 10.1093/nar/gks700
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of the smallest Apicomplexan genome from the human pathogen Babesia microti†

Abstract: We have sequenced the genome of the emerging human pathogen Babesia microti and compared it with that of other protozoa. B. microti has the smallest nuclear genome among all Apicomplexan parasites sequenced to date with three chromosomes encoding ∼3500 polypeptides, several of which are species specific. Genome-wide phylogenetic analyses indicate that B. microti is significantly distant from all species of Babesidae and Theileridae and define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
251
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(263 citation statements)
references
References 76 publications
(67 reference statements)
12
251
0
Order By: Relevance
“…Analysis of the pattern of hybridization revealed that the gene encoding BmAMA1 was present as a single-copy gene (data not shown). This result is further corroborated by the recently published B. microti genome sequence (36), which suggests the presence of a single copy of the BmAMA1 gene on chromosome 3. (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Analysis of the pattern of hybridization revealed that the gene encoding BmAMA1 was present as a single-copy gene (data not shown). This result is further corroborated by the recently published B. microti genome sequence (36), which suggests the presence of a single copy of the BmAMA1 gene on chromosome 3. (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The AMA1 sequence derived from gDNA of B. microti has a small 23-nucleotide intron compared to the sequence derived from cDNA. The presence of short introns is a common occurrence in B. microti; genome sequencing has revealed that about 70% of all B. microti genes contain introns of 20 to 25 bp in length (36). We found that the BmAMA1 gene sequence was highly conserved among B. microti parasites from Nantucket Island, MA.…”
Section: Discussionmentioning
confidence: 77%
“…The Plasmodium and Babesia genera are relatively closely related among the apicomplexans (1) (last common ancestor, ϳ55 million years ago [2]) ( Fig. 1A) and share similar features in their biology, including mechanisms for host cell invasion and metabolism (3)(4)(5)(6). Both Plasmodium and Babesia spp.…”
mentioning
confidence: 99%
“…These analysis shows that this species does not belong to none of the established genera -Babesia and Theileria -but to a separate genus [12].…”
Section: Typical Fi Nal Hosts and Vectors Of B Microti In Europe Arementioning
confidence: 86%